Isolation of indigenous Bacillus velezensis from aging tobacco leaves for improving the flavor of flue-cured tobacco - Shan, Xiao-Jie; Jin, Lifeng; Li, Feng; Yang, Sheng-Bing; Zhang, Xiao-Juan; Chai, Li-Juan; Gong, Jin-Song; Shi, Jin-Song; Lu, Zhen-Ming; Hu, Zong-Yu; Xu, Zheng-Hong (Frontiers in Microbiology, 2025)
IntroductionAging of flue-cured tobacco is a slow microbial fermentation process that usually lasts for 2–3 years, which plays an important role in improving the quality of final products.MethodsRe-dried tobacco leaves from seven Chinese regions were subjected to a controlled aging environment for 12 months. The bacterial community succession and volatile compounds dynamics in tobacco leaves throughout aging process were monitored. The main functional microorganisms were isolated from the tobacco leaves and inoculated into lower-grade tobacco leaves to evaluate their metabolic functions.ResultsSpearman’s rank correlation analysis revealed that Bacillus was a key genus driving aroma production. By using the pure culture method, strain Bacillus velezensis TB-1 with the best enzyme-producing capacity was screened from high-grade tobacco leaves. Furthermore, Bacillus velezensis TB-1 was applied to low-grade tobacco leaves for solid-state fermentation. GC-MS results showed a significant increase in volatile compounds in fermented tobacco leaves compared to unfermented controls. The contents of 2-methoxy-4-vinylphenol (clove and wood flavors), megastigmatrienone (tobacco and spicy aromas), 2-methyl-hexanoic acid (cream flavor) increased significantly. Sensory evaluation confirmed that fermentation with Bacillus velezensis TB-1 markedly enhanced tobacco leaf flavor quality.DiscussionThis study identified Bacillus velezensis as a core aroma-producing microorganism in tobacco aging, demonstrating its application for fermentation to enhance leaf quality, thus establishing a novel strategy for tobacco improvement.